PRAKTIK HAK KEKEBALAN DIPLOMATIK PEJABAT SENIOR NEGARA TERHADAP PELANGGARAN BERAT HAM MENURUT YURISPRUDENSI PENGADILAN INTERNASIONAL - Nadia Salsabila (BELLI AC PACIS, 2021)
This study examines the extend to the applicability of diplomatic immunity rights for senior officials against gross human rights violations they have committed. Toa achieve such aim, the author analysed the different types of immunity granted by international law to state officials, the reasons for the conferment of this immunity, and whether they apply in cases in which it is alleged that an official has committed an international crime. By using a statutory and case approach, the author examines several cases heard before international courts to compare the implementation of immunity rights. The author argues that both immunity ratione materiae and immunity ratione personae cannot be applied to cases that constitute gross violations of human rights. Moreover, instead did not agree with the argument which have been put forward by scholars and ICJ in support of the contrary.